Process Consolidation Of Boron Steam And Emitter Diffusion In Pnp Bipolar Transistor Fabrication - Abd.Wahab, Kader Ibrahim (2003)
Boron Steam is a process done after boron emitter diffusion for all PNP transistors and diodes. Boron emitter diffusion is a process to dope the emitter well with P-type dopant. The source of this dopant is in the form of liquid spun on the wafers and exposed to high temperatures. Boron steam is done to basically soften the residual liquid boron prior to cleaning for easy removal. This project will cover hardware comparison and recipe proposal that were used. The new consolidated process has resulted in comparable final in-line measurement of oxide thickness and test results. Reliability expectation was also met with 1000 cycles of Intermittent Operating Life test. Significant cost advantages were also achieved.